2018
DOI: 10.1116/1.5006866
|View full text |Cite
|
Sign up to set email alerts
|

Electron emission properties of graphene-oxide-semiconductor planar-type electron emission devices

Abstract: Local current-voltage estimation and characteristization based on field emission image processing of large-area field emitters

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…This is because of the voltage drop caused by the relatively high sheet resistance of the graphene gate electrode. Although we confirmed that electron emission occurs over the whole emission area by observing the electron emission pattern at a phosphor screen in a previous study, 20 for the case of a large emission area, the electron emission current at the center of the emission area would be smaller than that at the device edge because of the voltage drop at the center of the gate electrode. This would affect the uniformity of the electron emission of the GOS devices.…”
Section: ■ Experimental Sectionsupporting
confidence: 82%
See 3 more Smart Citations
“…This is because of the voltage drop caused by the relatively high sheet resistance of the graphene gate electrode. Although we confirmed that electron emission occurs over the whole emission area by observing the electron emission pattern at a phosphor screen in a previous study, 20 for the case of a large emission area, the electron emission current at the center of the emission area would be smaller than that at the device edge because of the voltage drop at the center of the gate electrode. This would affect the uniformity of the electron emission of the GOS devices.…”
Section: ■ Experimental Sectionsupporting
confidence: 82%
“…In addition, we observed that the electron emission efficiency of the GOS devices fabricated by Ga vapor-assisted CVD showed no dependence on the graphene electrode thickness for thicknesses ranging from 1.8 to 7 nm and was below 1% in our previous study. 20 Therefore, the emission efficiency difference cannot be fully explained by the thickness difference of the graphene electrode. Another possible explanation is the defects of the oxide layer causing the hopping conduction of the electrons.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…These excellent features of graphene suggest the ideal material for the gate electrode of the MOS type electron emission source. In fact, the efficiency of planar-type electron sources has been improved to 0.3~13 % by suppression of electron scattering using graphene gate electrode [27][28][29][30][31][32]. However, further improvement of the electron emission efficiency of the planar-type electron emission source has been required to obtain sufficient electron beam current from an emission area equivalent to the electron source sizes of the conventional electron guns.…”
mentioning
confidence: 99%